2021
DOI: 10.3390/antiox10020194
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase 5 Induces Changes in the Unfolded Protein Response in Human Aortic Endothelial Cells and in Endothelial-Specific Knock-in Mice

Abstract: Oxidative stress constitutes a key molecular mechanism in the development of cardiovascular diseases. A potential relationship between reactive oxygen species (ROS) driven by the NADPH oxidase family (NOX) and the unfolded protein response (UPR) has been postulated. Nevertheless, there is a lack of information about the crosstalk between NOX5 homologue and the UPR in a cardiovascular context. The main aim was to analyze NOX5-mediated ROS effects in the UPR and its importance in cardiovascular diseases. To this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…It works as a transition factor through cell cycle phases, the higher the E2f expression, the lower the proliferative stimuli that cells need to replicate [ 36 ]. In agreement with this, the reanalysis of a transcriptomic study performed by our group on HAEC infected with NOX5 adenovirus [ 19 ], shows that NOX5 promotes the upregulation of different E2f isoforms ( Supplementary Table S5 ). The E2f7 isoform, related with cells apoptosis and DNA damage [ 36 ], is the most overexpressed member.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…It works as a transition factor through cell cycle phases, the higher the E2f expression, the lower the proliferative stimuli that cells need to replicate [ 36 ]. In agreement with this, the reanalysis of a transcriptomic study performed by our group on HAEC infected with NOX5 adenovirus [ 19 ], shows that NOX5 promotes the upregulation of different E2f isoforms ( Supplementary Table S5 ). The E2f7 isoform, related with cells apoptosis and DNA damage [ 36 ], is the most overexpressed member.…”
Section: Discussionsupporting
confidence: 67%
“…NOX5 overexpression enhanced caspase 3/7 levels related with apoptosis, and decreased cell proliferation as it was observed in intact cells by xCELLigence. Our group previously reported that NOX5-β overexpression by this adenovirus in HAECs leads to apoptosis via UPR signaling [ 19 ]. Other groups have also described NOX5 as proapoptotic agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NOX5 upregulation and activation is related with many different processes, including the unfolded protein response [ 39 ], the management of lipid accumulation and insulin sensitivity [ 40 ] or the inflammation via COX2 activation and PG pathway induction [ 22 ]. In this context, the COX2 pathway may lead to brain ROS accumulation during aging [ 41 ] or after stroke [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cortes et al [ 13 ] study the potential crosstalk between NOX5-derived oxidative stress and the unfolded protein response (UPR) in endothelial cells and its impact on cardiovascular pathophysiology. In a transcriptomic study, gene ontology analysis revealed that NOX5 overexpression activates the UPR pathway.…”
mentioning
confidence: 99%